2003
DOI: 10.1046/j.1365-8711.2003.06630.x
|View full text |Cite
|
Sign up to set email alerts
|

Brown dwarfs and low-mass stars in the Pleiades and Praesepe: membership and binarity

Abstract: We present near‐infrared J‐, H‐ and K‐band photometry and optical spectroscopy of low‐mass star and brown dwarf (BD) candidates in the Pleiades and Praesepe open clusters. We flag non‐members from their position in K, I−K and J, J−K colour–magnitude diagrams (CMDs), and J−H, H−K two‐colour diagrams. In general, the dust‐free NextGen model isochrones of the Lyon Group fit the K, I−K CMDs well for stars with I−K∼ 1.5–3.5. However, Pleiades stars with K≃ 10.5–13 (MK≃ 5–7.5) are rather redder than the isochrones. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
4

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(95 citation statements)
references
References 74 publications
(107 reference statements)
8
83
4
Order By: Relevance
“…Extrapolating the observed frequency of visual companions assuming an overall Gaussian orbital period distribution, Gizis & Reid (1995) suggested that CF open cluster M⋆ 0.1 M ⊙ = 27 ± 16%. Photometric studies, which may be affected by a mass segregation selection effect, broadly support these results despite some significant scatter (Boudreault et al 2012, Converse & Stahler 2008, Lodieu et al 2007, Pinfield et al 2003.…”
Section: Multiplicity Frequencymentioning
confidence: 57%
“…Extrapolating the observed frequency of visual companions assuming an overall Gaussian orbital period distribution, Gizis & Reid (1995) suggested that CF open cluster M⋆ 0.1 M ⊙ = 27 ± 16%. Photometric studies, which may be affected by a mass segregation selection effect, broadly support these results despite some significant scatter (Boudreault et al 2012, Converse & Stahler 2008, Lodieu et al 2007, Pinfield et al 2003.…”
Section: Multiplicity Frequencymentioning
confidence: 57%
“…And thus the bifurcation of our int-g late-M sample may reflect the conflation of a younger population (e.g., 2MASSI J0019+4614 is a member of the ≈125 Myr AB Dor group) and an older one. An additional consideration is that the M7-M8 range is where Dobbie et al (2002) have suggested the mass-luminosity relation changes due to the onset of dust formation, as inferred from the luminosity function of young clusters (see also Pinfield et al 2003;Chappelle et al 2005). So the int-g bifurcation may also reflect dust opacity variations.…”
Section: Dispersion In Absolute Magnitudesmentioning
confidence: 99%
“…There is no proof that these BDs were ejected from forming protostellar systems. The large BD binary fraction of 15% (Martín et al 2003, Pinfield et al 2003) is furthermore hardly explained by ejection scenarios (Whitworth & Goodwin 2005). It thus appears plausible that at least some of the single brown dwarfs may have formed by processes similar to those by which normal stars form, i.e.…”
Section: Introductionmentioning
confidence: 99%